2014
DOI: 10.1002/ijc.28697
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing ofSFRP1andSFRP5by hepatitis B virus X protein enhances hepatoma cell tumorigenicity through Wnt signaling pathway

Abstract: Secreted frizzled-related proteins (SFRPs) are antagonists of the Wnt signaling pathway whose epigenetic downregulation have been shown to be involved in hepatocarcinogenesis. However, dysregulation of SFRPs induced by hepatitis B virus (HBV) X protein (HBx) has never been studied in HBV-related hepatocellular carcinoma (HBV-HCC). In this study, we sought to determine the clinical significance and underlying mechanism of HBx-induced SFRPs dysregulation in hepatoma cells and HBV-HCC patients. Our results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 32 publications
(47 reference statements)
3
46
0
Order By: Relevance
“…In mammals, DNA methylation is mainly catalyzed by DNMT1, DNMT3a and DNMT3b. Several studies have reported that HBV could increase the expression of DNMT1 and DNMT3a, resulting in aberrant promoter methylation of E-cadherin, p16INK4A, SFRP1and SFRP5 (Lee et al 2005;Jung et al 2007;Xie et al 2014). Consistent with these studies, this study found that GSTP1 promoter methylation was positively correlated with DNMT1 mRNA, DNMT3a mRNA, TNF-α, MDA, HBeAg, ALT, AST and TBIL in patients with CHB.…”
Section: Discussionsupporting
confidence: 89%
“…In mammals, DNA methylation is mainly catalyzed by DNMT1, DNMT3a and DNMT3b. Several studies have reported that HBV could increase the expression of DNMT1 and DNMT3a, resulting in aberrant promoter methylation of E-cadherin, p16INK4A, SFRP1and SFRP5 (Lee et al 2005;Jung et al 2007;Xie et al 2014). Consistent with these studies, this study found that GSTP1 promoter methylation was positively correlated with DNMT1 mRNA, DNMT3a mRNA, TNF-α, MDA, HBeAg, ALT, AST and TBIL in patients with CHB.…”
Section: Discussionsupporting
confidence: 89%
“…DNA methylation of CpG sites in the promoter region has been demonstrated to be responsible for the downregulation of sFRP genes in many forms of cancer and leukemia. 21,[32][33][34][35][36] Our data is in line with previous studies, showing that transcriptional silencing of sFRP1 correlates with therapy resistance and progressive disease. 29 We suggest a model of hematopoiesis in which Wnt antagonists sFRP1 and WIF1 normally play a central role in downregulating β-catenin in granulocyte-macrophage progenitors.…”
Section: Discussionsupporting
confidence: 92%
“…For example, expression of SFRP5 and SFRP1 was markedly reduced in HBx-infected cells. 28 In vitro analysis confirmed the presence of hypermethylated promoter regions of SFRP1 and SFRP5 genes in HBx-expressing hepatoma cells. Detailed assays provided evidence of HBx-directed binding of DNMT3A and DNMT1 to the promoter regions of SFRP5 and SFRP1.…”
Section: Wnt Antagonistsmentioning
confidence: 78%